Simple reaction time: how it relates to body mass index (BMI), gender and handedness in Ghanaian students. J Med Sci, Volume 49, No. 1, 2017 January: 1-7 Corresponding author: ampomahbrown@yahoo.com Simple reaction time: how it relates to body mass index (BMI), gender and handedness in Ghanaian students - Ato Ampomah Brown; Leonard Derkyi-Kwarteng; Christian K Ackom; Ernest Addae; Francis Newton; Dennis Amoah; Dennis Nartey Blemano (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
The purpose of this study was to examine the relationship between gender, handedness and body mass index (BMI) with simple reaction time. The study was conducted amongst 501 (232 females and 269 males) untrained University of Cape Coast students, Ghana whose ages ranged from 17-29 years. In this study it was found that males had faster reaction times than females, likewise the mean reaction time of the left hand was also faster than that of the right hand. There was however no significant difference in the mean reaction time across BMI classes In conclusion, simple reaction time is influenced by gender and handedness but appears not to be influence by BMI